On Java Road : a novel - Osborne, Lawrence, 1958- (Hogarth, 2022)
"After twenty years as a journalist in Hong Kong, ex-pat Englishman Adrian Gyle has very little to show for it. Evenings are whiled away with soup dumplings and tea at Fung Shing, the restaurant downstairs from his home on Java Road, that "most melancholy street in the city, the street where the dead congregated." It is through these jaded eyes that Gyle watches the city around him--once overflowing with wine dinners and private members' clubs--erupt in violence as pro-democracy demonstrations hit ever closer to home. But just as Gyle prepares to turn his back on Hong Kong, he finds one last intrigue: the alluring Rebecca, the new girlfriend of one of his oldest friends, and a student involved in the protests. When her body mysteriously turns up in the local morgue, Gyle finds that old familiar urge to investigate. As he pieces together Rebecca's final days and hours, Gyle must tread carefully through a volatile world of truth and betrayal. On Java Road tells the story of a search for a missing woman in a vanishing city, and a man stood between cultures, as an old world breaks to a new dawn"--